Efek Diuretik dan Daya Larut Batu Ginjal Dari Ekstrak Daun Mangkokan (Nothopanax scutellarium. Merr) - Elisma Elisma; Fitri Maya Sari; Helmi Arifin (STIFARM Padang, 2010)
Research on the effects of diuretics and solubility of kidney stones of Mangkokan leaf (Nothopanax scutellarium Merr.) extract has been done. Testing the solubility of kidney stones performed on 4 groups of test animals, namely the control group (without extract), The treatment dose groups of 0.5%, 1%, and 2%. Level of kidney stones are dissolved in the control group, 0.5%, 1% and 2% are 0.00521%, 0.01232%, 0.02433% and 0.05669% respectively. These result indicate a difference in dissolving kidney stones. Diuretic effect tested on 15 white male rats were divided into 5 groups of tests, one positive control group (furosemide), 1 negative control group (tween 80 1%), 3 treatment groups (doses of 125; 250 and 500 mg/kg BW). The result showed that all of three doses of extract have diuretic effect.